Tissue culture, histological and pigment analysis of Hylocereus polyrhizus (Weber) Britton and Rose / Ummi Nur Ain Abdul Razak - Ummi Nur Ain, Abdul Razak (2017)
An optimum protocol for culturing Hylocereus polyrhizus (Weber) Britton and Rose for in vitro regeneration and mass propagation was established in the present study. A comparative histological analysis between in vivo and in vitro grown plants was also successfully investigated. Stem explants cultured on MS medium supplemented with 6-benzylamino purine (BAP), α-Naphthaleneacetic acid (NAA) and Kinetin were placed both vertically and horizontally. MS medium supplemented with low concentration of BAP (0.2 mg/L) gave the highest formation of multiple shoots (8.07 ± 0.721) when stem explants were horizontally cultured. Low concentration of Kinetin (0.2 mg/L) induced the longest shoots in average (1.608 ± 0.128 cm) which was also cultured in horizontal position. Combination of 0.1 mg/L of BAP and 0.1 mg/L of α-Naphthaleneacetic acid (NAA) gave the highest average number of roots (3.031 ± 0.237) in vertical culture position. The combination of 0.5 mg/L of BAP and 0.1 mg/L of NAA resulted in the longest root formation when cultured in horizontal position. In callus induction, the highest percentage (100%) was obtained in MS medium supplemented with combinations of 1.0 mg/L BAP and 0.1 mg/L 2, 4-D; 1.0 mg/L BAP and 1.0 mg/L 2, 4-D and 2.0 mg/L BAP with 1.0 mg/L 2, 4-D. The lowest percentage (27.0 ± 0.082 %) was observed when the stem explants were cultured on MS medium supplemented with 2.0 mg/L 2, 4-D. Green callus was observed on MS medium supplemented with 1.0 mg/L BAP and 0.5 mg/L 2, 4-D; 1.0 mg/L BAP and 1.0 mg/L 2, 4-D, and 2.0 mg/L BAP with 1.0 mg/L 2, 4-D. In the synthetic seed studies, maximum germination (100%) was obtained when the beads were germinated on MS basal medium and emergence of shoots was observed on Day 10. No development of complete plantlets was observed when the hormones were added in the matrix of encapsulated beads. The viability of the beads decreased with the increasing of the storage period. The hardening process of synthetic seed showed negative results with fungal infection. Complete plants were successfully acclimatized in the combination of red soil, black soil and cocoa peat (1:1:1) with 83.3% survival rate. Quartz or silicon oxide (47.33%) was the most abundant element in soil used in acclimatization as examined by X-ray diffractometry (XRD). The multielements such as Si, Al, Fe, Ca, K, Mg, Na, Cu, Zn, Rb, Sr, Zr, Nb and Cl were presence in the soils analyzed by X-ray fluorescence spectrometry (XRF) measurements. For histological analysis, stems and roots derived from in vivo and in vitro grown plants showed differences in cortical bundle structures, cortex and stomata structures. Histological studies were carried out to compare in vivo and in vitro plants structures and to monitor any occurrence of somaclonal variation. The established protocol of regeneration system exhibited a high potential in plant production and can help to fulfil the market demand. For pigment analysis, betacyanin pigments extracted from pulp using 80% acetone as solvent at pH 1.0 gave the highest betacyanin content. Betacyanin content decreased when stored under exposure of light compared to dark storage. In addition, increasing concentration of NaCl decreased the absorbance values at faster rates for betacyanin-coated glass slides. The method for detection of betacyanins pigment stability and effectiveness of betacyanins pigments used as natural colorants for coating application was beneficial, recent and novel for environmental friendly and natural plant based products development.